Short and long-time prognosis of hypertensive crisis - Paavonsalo, Ville (My University, 2025)
We studied the short and long-time prognosis of hypertensive crisis (HTN-C) and the leading clinical risk factors of HTN-C related mortality. We performed a literature search using three commonly used scientific databases including 39 original research articles for our systematic review. We performed a random effect meta-analysis to estimate the mortality rates for different subtypes of HTN-C and hazard ratios for clinical covariates with HTN-C related mortality. The overall mortality rate was 0.06 events per person year (95% CI 0.03-0.12) after HTN-C. The short-time mortality rate may be higher compared to the long-time mortality rate. More severe forms of HTN-C may also lead to higher mortality rates. For each 10-year increase in age, we observed 1.36-fold (P<0.001) higher mortality. Sex and baseline systolic blood pressure were not significantly associated with mortality. Hypertensive crisis is associated with an increased mortality rate and age is the leading clinical covariate for mortality risk.
Keywords: Blood pressure, Hypertension, hypertensive crisis, systematic review